Managing Acute and Chronic Illness in Nursing: A Review - Jadhav, Vaishali (Innovational: Journal of Nursing and Healthcare, 2025)
Acute and chronic illnesses represent two distinct categories of health conditions that require comprehensive and differentiated nursing approaches. Acute illnesses develop rapidly, present with sudden and often severe symptoms, and typically resolve within a short duration when timely medical intervention is provided. In contrast, chronic illnesses progress slowly, persist for months or years, and require continuous management to prevent complications and maintain quality of life. This review explores the essential role of nursing care in managing both acute and chronic illnesses, emphasizing the differences in assessment, intervention strategies, patient needs, and care coordination. In acute illness management, nursing responsibilities include rapid assessment, stabilization, symptom control, prevention of complications, and shortterm patient education. Chronic illness management requires ongoing monitoring, long-term symptom control, lifestyle modification support, emotional and psychological counseling, and coordination with multidisciplinary teams. The review further highlights common challenges faced by nurses, such as limited resources, patient adherence issues, emotional burdens on caregivers, and the influence of cultural and socioeconomic factors on care outcomes. The integration of technology—including telehealth, electronic health records, and mobile health applications—has emerged as an important tool to enhance patient engagement and improve continuity of care. Case examples of pneumonia and diabetes management demonstrate the practical application of nursing interventions across acute and chronic conditions. The review concludes by emphasizing the importance of continuous nursing education, evidence-based practice, patient-centered care, and community based support to optimize health outcomes for individuals living with acute and chronic illnesses.